Elettaria cardamomum: caracterização, toxicidade, atividade antimicrobiana e sinérgica do óleo essencial frente a Aeromonas hydrophila - Teixeira, Cristiane Antunes (2021)
Characterized as being Gram-negative bacteria, Aeromonas species can cause several infections, which include urinary tract infections, pneumonia, meningitis, sepsis, among others. Drugs such as Florfenicol (FFC) and oxytetracycline (OTC) have been shown to be effective against A. hydrophila infections. However, the use of antimicrobials as a preventive measure is much questioned due to their side effects, which can alter the intestinal microbiota and induce bacterial resistance through defense mechanisms. In this context, medicinal plants have played an important role in health care as they are a source of new potentially antimicrobial substances. These substances can be found in the essential oils of these medicinal and aromatic plants. The essential oil of cardamom (Elettaria cardamomum) has monoterpenic constituents that demonstrate anti-inflammatory, antimicrobial, anticancer, antioxidant and gastroprotective activities. Therefore, this study aimed to characterize the essential oil of E. cardamomum, evaluate its antimicrobial activity and synergistic activity when associated with FFC and OTC, as well as its cyto and genotoxicity. The essential oil was obtained through the company FERQUIMA®, and its extraction was carried out from the plant's seeds by the water vapor drag method. The characterization of the essential oil was determined by gas chromatography. The antimicrobial activity against Aeromonas hydrophila was performed using the broth microdilution methodology. Through the Checkerboard technique, the synergism of the essential oil in combination with FFC and OTC was evaluated. Cytogenotoxicity was performed by MTT, Dichlorofluorescein diacetate, DNAPicoGreen® and Nitric Oxide assays. The chromatographic profile of the essential oil resulted in 16 substances, where the major analytes were alpha-terpenyl acetate (40%), eucalyptol (33%) and linalyl acetate (5%). Through susceptibility tests, the effectiveness of the essential oil as a bactericidal agent against A. hydrophila species was proven. Concentrations were prepared from serial dilutions ranging from 4.65 µg/mL to 0.009 µg/mL. When combined with the antimicrobials Florfenicol and oxytetracycline, synergism and additive action result, respectively. The evaluation of the cytogenotoxicity of the oil at bactericidal and bacteriostatic concentrations did not cause damage to human mononuclear cells. The absence of previous work regarding the essential oil of E. cardamomum against A. hydrophila makes this work innovative and a source of studies for future experiments on antimicrobial activity and other biological properties.